Remodeling of extracellular matrix of the lamina propria in the uninvolved human rectal mucosa 10 and 20 cm away from the malignant tumor. Issue 7 (July 2017) - Despotović, Sanja Z; Milićević, Novica M; Milošević, Dragoslav P; Despotović, Nebojša; Erceg, Predrag; Svorcan, Petar; Schumacher, Udo; Ullrich, Sebastian; Mihajlović, Gordana; Kalem, Dragan; Marković, Srđan; Lalić, Ivana M; et al.
In recent years, it has been demonstrated that malignancy arises and advances through the molecular interplay between tumor cells and non-malignant elements of the tumor stroma, that is, fibroblasts and extracellular matrix. However, in contrast to the mounting evidence about the role of tumor stroma in the genesis and progression of the malignant disease, there are very few data regarding the uninvolved stromal tissue in the remote surrounding of the tumor. Using the objective morphometric approach in patients with adenocarcinoma, we demonstrate the remodeling of extracellular matrix of the lamina propria in the uninvolved rectal mucosa 10 and 20 cm away from the neoplasm. We show that the representation of basic extracellular matrix constituents (reticular and collagen fibers and ground substance) is decreased. Also, the diameter of empty spaces that appear within the extracellular matrix of the lamina propria is increased. These spaces do not represent the blood or lymphatic vessel elements. Very likely, they reflect the development of tissue edema in the remote, uninvolved lamina propria of the mucosa in patients with the malignant tumor of the rectum. We hypothesize that the remodeling of extracellular matrix in lamina propria of the rectal mucosa may increase its stiffness, modulating the mechano-signal transduction, and thus promote the progression of the malignant disease.